PTH-030 Outcomes of hemospray use in peptic ulcer upper gastrointestinal bleeds: Outcomes from the hemospray registry. (June 2019) - Hussein, Mohamed; Alzoubaidi, Durayd; Fraile, Miguel; Fernandez-sordo, Jacobo Ortiz; Ragunath, Krish; Rusu, Radu; Dunn, John; Rey, Johannes; Gulati, Shraddha; Hayee, Bu'Hussain; Dixon, Selena; Moreea, Sulleman; et al.
Abstract : Introduction: Peptic ulcers are the commonest cause of upper Gastrointestinal bleeding (UGIB). Hemospray (Cook Medical, North Carolina, USA) is a novel haemostatic powder aimed to treat UGIB. The aim of this study is to look at outcomes in patients with peptic ulcer GI bleeds treated with hemospray in 13 centres. Methods: Data was prospectively collected on hemospray use in UGIBs in the UK, France and Germany (Jan'16-Sept'18). Hemospray was used for peptic ulcer UGIBs as a monotherapy, dual-therapy with standard haemostatic techniques or rescue therapy. Haemostasis was defined as cessation of bleeding within 5 minutes of hemospray application. Results: 196 patients with UGIBs secondary to peptic ulcers were recruited (133 M, 63 F, 123/196(63%) duodenal, 44/196(22%) gastric, 29/196(15%) oesophageal). Immediate haemostasis was achieved in 171/196(87%) patients. The median rockall score was 7 (IQR, 6–8). Rebleeding rates were significantly lower in forrest 2a relative to current predicted rebleeding rates based on forrest classifications, 2/21(10%, P<0.005). In the 25/196(13%) patients who did not achieve haemostasis 18/25 (72%) were Forrest 1b ulcers. In the total cohort, 33/169(20%) had a rebleed, median rockall score was 7(IQR, 7–8). Outcomes with different Forrest classifications (table 1 ) Conclusions: Hemospray is effective in achieving immediate haemostasis in peptic ulcer UGIBs. The baseline Blatchford/rockall scores in our cohort are high with patients recruited from tertiary centres with high-risk cases. The rebleeding and mortality rates are in keeping/below the predicted rate based on the scores. The best outcome with hemospray was with forrest 2a ulcers.